Three-wavelength system for practical application in skin oximetry: simultaneous equations with prediction-correction approach - Audrey Huong; W. Mahani Hafizah W. Mahmud; Xavier Ngu (Institute of Advanced Engineering and Science, 2020)
This paper presented the use of a three-wavelength system coupled with a prediction-correction model for the measurement of a person’s tissue oxygen levels and in the eﬀorts towards the development of a ﬁeld-portable system. This study considered light wavelength of market-available emitters in the range 500 − 650 nm for its practical implementation. This approach required the use of light attenuation and hemoglobin absorptivity information of three diﬀerent wavelengths in determining tissue oxygen saturation value, StO2. It was found through the analysis of results using Monte Carlo method that considerable improvement in the accuracy of the predictions was obtained using the corrective models (ρ =0.874). The low mean prediction errors of similar magnitude, not exceeding 4 %, given by two wavelength combinations 538, 560, 633 nm and 538, 560, 650 nm were observed for signals with signal-noise ratio (SNR) of down to 30 dB. A signiﬁcant statistical diﬀerence was found between the prediction errors and the wavelength combination used under this noise condition (ρ =0.011). This work concluded that the ﬁndings of this study provide insights into technology implementation of skin oximetry and the possible impacts it might have in medical arena.